1991
DOI: 10.1007/bf00983768
|View full text |Cite
|
Sign up to set email alerts
|

Wind-tunnel study on attraction inhibitor in maleColeophora laricella Hbn. (Lepidoptera: Coleophoridae)

Abstract: Modifying effects of (Z)-5-decenyl acetate, an attraction-inhibitor of maleC. laricella, were studied at different levels of the pheromonal behavioral sequence. When blended with the attractant alcohol (Z)-5-decen-1-ol, 0.001% acetate significantly reduced and 1% almost abolished orientation flights followed by landing at the source. By contrast, 1000% of the acetate placed 5 cm apart did not suppress orientation flights to the alcohol source. Differential modifying effects of the acetate in blends vs. separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
2
22
2
Order By: Relevance
“…Thus, reducing the modifier's release rate should at least partially duplicate the effects of displacing the modifier, particularly regarding effects 1 and 3 above. In support of this inference, spatial displacement of a modifier (either a synergist or an inhibitor) from the release point of an insect semiochemical generally produces the same outcome as reducing the dose of or eliminating the modifier: displacement of inhibitors increases (McLaughlin et al 1974;Witzgall and Priesner 1991;Liu and Haynes 1992;Rumbo et al 1993;Potting et al 1999), whereas displacement of synergists reduces insect responses to a semiochemical (Linn and Gaston 1981;Byers 1987;Lux et al 1994). However, in experiment 3, reducing the dose of (+)-endo-brevicomin at the center trap caused a reduction in D. frontalis catches at both the center and the adjacent traps, not an increase in catch at the center trap as would be predicted if the relatively higher catch in the outer traps was attributable simply to a relatively lower concentration of (+)-endo-brevicomin at these locations.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, reducing the modifier's release rate should at least partially duplicate the effects of displacing the modifier, particularly regarding effects 1 and 3 above. In support of this inference, spatial displacement of a modifier (either a synergist or an inhibitor) from the release point of an insect semiochemical generally produces the same outcome as reducing the dose of or eliminating the modifier: displacement of inhibitors increases (McLaughlin et al 1974;Witzgall and Priesner 1991;Liu and Haynes 1992;Rumbo et al 1993;Potting et al 1999), whereas displacement of synergists reduces insect responses to a semiochemical (Linn and Gaston 1981;Byers 1987;Lux et al 1994). However, in experiment 3, reducing the dose of (+)-endo-brevicomin at the center trap caused a reduction in D. frontalis catches at both the center and the adjacent traps, not an increase in catch at the center trap as would be predicted if the relatively higher catch in the outer traps was attributable simply to a relatively lower concentration of (+)-endo-brevicomin at these locations.…”
Section: Discussionmentioning
confidence: 90%
“…An additional nearby attractant source provides intermittent stimulation with pure attractant, and restores upwind attraction, in codling moth (Fig. 1) as in other species (Witzgall and Priesner 1991;Liu and Haynes 1993;Fadamiro et al 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Pheromone antagonists must be perceived simultaneously to suppress upwind orientation behaviour and source location (Witzgall and Priesner 1991;Liu and Haynes 1993), as male moths distinguish between pheromone and antagonist odour filaments at an astounding temporal and spatial resolution (Fadamiro et al 1999). The respective synergists and antagonists are perceived via specialized antennal receptor cells (Priesner 1986;CossØ et al 1998), and differences in the processing of pheromone synergists and antagonists in the antennal lobe are becoming apparent (Christensen et al 1995;Hansson et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Along with our behavioral data, the colocalization of the neurons suggests that the binary mixture constitutes an ecologically significant signal, assuming that selective pairing of ORNs is adaptive and not due to chance. Some male moths have a remarkable ability to distinguish odor filaments from different sources with extremely high spatiotemporal resolution (Fadamiro et al, 1999;Witzgall and Priesner, 1991). It was suggested that such amazing feats depend on ORNs being located within the same sensillum (Fadamiro et al, 1999), which is common among pheromone agonist/antagonist neurons in Lepidoptera Larsson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%